Study of the Mechanism of Interaction of Microwave Plasma Discharge with Solutions of Organic Substances; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Shiyan L. N. Lyudmila Nikolaevna; Zherlitsyn A. G. Aleksey Grirorievich; Magomadova S. O.; Lazar C. S. (Discharge and Plasma-Beam Technology, 2016)
Title screen